Questionnaire‐based survey in a developing country showing noncompliance with paediatric gastro‐oesophageal reflux practice guidelines. (23rd November 2016) - Manasfi, Hayat; Hanna‐Wakim, Rima; Akel, Imad; Yazbeck, Nadine
Abstract: Aim: This 2015 study investigated whether Lebanese paediatricians diagnosed and managed gastro‐oesophageal reflux disease (GERD) in infants and children in accordance with the 2009 guidelines from the North American and European Societies for Paediatric Gastroenterology, Hepatology and Nutrition. Methods: Paediatricians members of the Lebanese Order of Physicians with updated email addresses were invited to complete a web‐based survey between September and November 2015, to assess their knowledge and management of GERD. Results: Responses were received from 114 of the 543 paediatricians, and 96 were analysed. Only two respondents complied fully with the international guidelines. The majority diagnosed GERD in infants based solely on their medical history and examination. Moreover, nearly two‐thirds of the respondents would start an empiric trial with acid suppression. Around half of the respondents considered proton pump inhibitors to be the mainstay of GERD treatment. Conclusion: This was the first Lebanese study that surveyed the management of paediatric GERD. Only 2.1% of the paediatricians followed the guidelines on the evidence‐based management of GERD. This highlights the need for studies to assess barriers to guideline implementation and the development of new guidelines accounting for regional factors, mainly the cost of investigations and prevalence of medical insurance.